Political Sociology - Wood, James (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
In this course in political sociology, we will study three related topics: (1) the distribution of power in the United States; (2) the organization and mobilization of political groups; and (3) an analysis of one political movement, the student movement.